2014
DOI: 10.1039/c4cp00061g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of laser-assisted carbon nanotube growth

Abstract: Laser-assisted chemical vapour deposition (CVD) growth is an attractive mask-less process for growing locally aligned carbon nanotubes (CNTs) in selected places on temperature sensitive substrates. The nature of the localized process results in fast carbon nanotube growth with high experimental throughput. Here, we report on the detailed investigation of growth kinetics related to physical and chemical process characteristics. Specifically, the growth kinetics is investigated by monitoring the dynamical change… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 59 publications
(121 reference statements)
2
11
0
Order By: Relevance
“…Most studies reported on an increase of the growth rate of nanotubes with raising the pressure of gaseous carbon precursor: C 2 H 4 [159,164,175177], C 2 H 2 [161,178179], CH 4 [180] and C 2 H 5 OH [154155]. The same trend was reported in theoretical work [205].…”
Section: Reviewsupporting
confidence: 61%
See 4 more Smart Citations
“…Most studies reported on an increase of the growth rate of nanotubes with raising the pressure of gaseous carbon precursor: C 2 H 4 [159,164,175177], C 2 H 2 [161,178179], CH 4 [180] and C 2 H 5 OH [154155]. The same trend was reported in theoretical work [205].…”
Section: Reviewsupporting
confidence: 61%
“…This was explained by a change of the kinetic regime of the nanotube growth from gas-phase diffusion limited to surface processes limited [155]. The authors of [177] observed linear dependences of the growth rate on precursor pressure with different slopes at low and high pressures. This was explained by the fact that at low precursor pressures the kinetic regime of the tube growth was surface diffusion limited and at high pressures – dissociation limited [177].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations